Cash operating income and liquidity management for dairy farms - B.D. Elliott; Michael R. Langemeier; Allen M. Featherstone (Kansas Agricultural Experiment Station Research Reports, 1995)
Net cash flow measures the amount of cash remaining after all cash expense obligations are satisfied. This cash is available for additional farm investment, off-farm investment, family living, and additional debt repayment. A 5- year average monthly cash flow statement was used to determine net cash flow for 19 Kansas dairy farms. Results indicated that excess cash and debt were used primarily to invest in machinery, vehicles, and nonfarm assets and increase the allocation for family living. Investments in land and buildings increased moderately during the study period.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Investment; Liquidity; Cash flow